CHARACTERISTICS OF CITATIONS USED BY HUMANITIES RESEARCHERS - Awang Ngah, Zainab; Goi, Sook Sze (Malaysian Journal of Library and Information Science, 1997)
Analysis of 5,610 citations from 104 master’s degree and doctoral dissertations submitted to the University of Malaya between 1984 and 1994 in the humanities (religion and philosophy; history; language and literature) has been conducted. The average citation per dissertation in various humanities fields, are 56.7 for religion and philosophy; 102 for history and 45.3 for language and literature. Over 52% (2,927) of the citations were to books, 23.55% (1,321) to journal articles, 9.43% (529) to book chapters and 6.24% (350) to theses. A total of 4,766 (89.94%) authors of the citations were single authors and 700 authors formed the core authors contributing a total of 2,160 (36.59%) of total citations. The use by humanities researchers of a wider number of journals and book titles indicate that they need to use a greater number of sources for their research information needs. More than 50% of the citations aged between 1 to 20 years and some more than 100 years. Researchers use a high percentage of documents in the English language even though about 66% of the dissertations were written in the Malay language. The references by and large are of Malaysian or Asian in origin reflecting resource needs of these researchers.